PENGARUH CORE STABILITY DAN MICRO WAVE DIATHERMY TERHADAP NYERI SPONDYLOARTHROSIS LUMBAL - Jhon Roby Purba; Surya Syahputra Berampu; Rostime Hermayerni Simanullang (Jurnal Online Keperawatan Indonesia, 2021)
Lumbar spondyloarthrosis is low back pain caused by degeneration of the discs, facet joints in the lumbar, so that there is pressure on the intervertebral foramen which will cause osteophytes where this causes irritation, it will cause tissue inflammation or can also occur pressure on the cauda equine. In other conditions, pain can also be caused by spasm of the muscles causing ischemia, ischemia causes pain.Perpuse: the aim of this study is analyzed effect of Core Stability and Micro Wave Diathermy to reduce pain on patients with Lumbar Spondyloarthrosis.Method: Design of this study is a eksperimental studyPre and Post Test Group Design without control group, used a total sampling teqhniqe and 12 respondents. Before and after is done intervention, measurement of pain scale of respondens. Result: Wilcoxon range test is analized data in this study with p value = 0.002 ( p<0.05).It is mean, there is a significant effect of Core Stability and Micro Wave Diathermy to reduce pain on patients with Lumbar Spondyloarthrosis. Conclusion:conclusion of this study are the core stability exercise and micro wave diathermy can reduce pain in patients with lumbar spondyloarthrosis. The suggestion in this study is to increase the number of respondents for the further reseaerch so they can represent a wider representative.